The new Refugium Botanicum. Maxillariella (Maxillaria) tenuifolia - Fernández Campos, Melania (2017)
Maxillariella tenuifolia (Lindl.) M.A. Blanco & Carnevali, Lankesteriana 7(3): 530. 2007. Basionym: Maxillaria tenuifolia Lindl., Edwards’s Botanical Register 23: sub. t. 1986. 1837. Type: “a native of Mexico, in the vicinity of Vera Cruz”, Hartweg s.n. (holotype, K).Epiphytic or terrestrial, straggling, pendent or ascending herb, up to 80 cm long. Roots flexuous, yellowish, produced from the pseudobulb. Rhizome concealed by appressed, imbricating, scarious sheaths. Pseudobulbs 1–8 cm or more apart on the rhizome, cylindric to fusiform, somewhat compressed, rugose, 2–6 cm long, 1–2 cm wide, apically unifoliate, subtended by 1 or more lanceolate-triangular, acute, imbricating, stiffly scarious sheaths